Konzept und Raum. - Osterwold, Tilman; Kunstverein Stuttgart, Stuttgart (Stuttgart : Kunstverein Stuttgart, 1977)
Freiman, Christoph ; Maier-Aichen, Hansjerg ; Nestler, Wolfgang ; Prager, Heinz-Günter ; Ruthenbeck, Reiner
kunstcatalogus